Food safety the science of keeping food safe - Shaw, Ian C. (Hoboken, NJ John Wiley & Sons, 2018)
Food safety is a multi-faceted subject, using microbiology, chemistry, standards and regulations, and risk management to address issues involving bacterial pathogens, chemical contaminants, natural toxicants, additive safety, allergens, and more. This revised edition has been updated with the latest information on food safety. It addresses all the topics pertinent to a full understanding of keeping the food we eat safe. Each chapter of Food Safety: The Science of Keeping Food Safe, Second Edition proceeds from introductory concepts and builds towards a sophisticated treatment of the topic, allowing the reader to take what knowledge is required for understanding food safety at a wide range of levels. Illustrated with photographs and examples throughout, this new edition also boasts 4 new chapters covering radioactivity in food; food terrorism; food authenticity; and food supplements.--Provided by publisher.
Includes bibliographical references and index.
Keywords: Food -- Analysis; Food contamination; Food -- Safety measures